Contribution of Prakerin, Entrepreneurship Learning Outcomes, and Soft Skills Towards Students' Interest in Entrepreneurship - Defelinu Harefa; M. Giatman; Ambiyar; Dedy Irfan (Postgraduate, University of Mataram, 2025)
Interest in entrepreneurship is a focus on entrepreneurship where there is a feeling of liking and accompanied by a desire to learn. Interest in entrepreneurship arises because of knowledge and information about entrepreneurship which is then continued to participate directly. This study aims to analyze the relationship between Prakerin experience, entrepreneurship learning outcomes, and Soft Skills on the entrepreneurial interest of students of Private Vocational High Schools of the Nias Regional Government. The type of research This study uses a quantitative approach with a correlational method. The goal is to measure the strength of the relationship between three independent variables. The results Entrepreneurship learning outcomes show a very strong and significant relationship (correlation 0.826; contribution 68.30%). Mastery of entrepreneurship material is the most influential factor in shaping entrepreneurial interest. The regression equation Ŷ = 0.18 + 0.82 X₂ shows a significant impact of increasing entrepreneurial learning outcomes on entrepreneurial interest. Soft skills also have a strong and significant positive relationship (correlation 0.708; contribution 50.20%). Interpersonal and intrapersonal skills, such as communication, leadership, teamwork, and adaptability, play a crucial role in encouraging students to choose the entrepreneurial path. The regression equation Ŷ = 0.38 + 0.61 X₃ shows that developing soft skills will significantly increase entrepreneurial interest.